THE USE OF PROCESS GENRE TECHNIQUE TO IMPROVE WRITING SKILL - ferri hidayad; Ariya Agustin; Muhammad iqbal; M Bambang Purwanto (Language and Education Journal, 2023)
This study was conducted to evaluate the outcomes of process-genre training in the EFL writing course. It also looked at how they used rhetorical devices and techniques in their essay. Additionally, the success of the intervention was evaluated according to how the pupils perceived it. At SMP N 2 Sungai Lilin's eighth grade, it was circumscribed. A quasi-experimental design was used to achieve this. Using the simple random sample procedure, Sections A (N=42) and C (N=41) comprised the study's experimental group (EG) and control group (CG), respectively. While the CG received the customary writing instruction, the EG was exposed to process-genre intervention. Data were gathered using two research instruments: an interview and a pre-post intervention writing exam. Accordingly, the experimental and controlling technique was carried out. The textbook for English students in grade 8 served as both an EG and CG teaching tool. To compare the test results between the two groups at the pre-post test, an independent samples t-test was used, and a paired samples t-test was used to compare test results between groups. Additionally, both qualitative and quantitative data analysis techniques were used. According to the study's conclusions, teaching process-genre writing in EFL writing classrooms is a beneficial instructional strategy. Students made an effort to use rhetorical techniques when composing their essays. The impact on students' attitudes toward process-genre writing training was positive. When implementing the training in their writing classroom, EFL teachers should be skilled and competent. Finally, it is advised to do additional study by lengthening the intervention period to examine the effects of process-genre based writing training as an instructional strategy in EFL writing classrooms.